Prediction of surgical site infection in spine surgery - Valery M. Haydarov; Alexandr N. Tkachenko; Irina A. Kirilova; Djalolidin Sh. Mansurov (Хирургия позвоночника, 2018)
Objective. To analyze prognostic factors for the development of surgical site infection following spine surgery and evaluate rating values for each of them. Material and Methods. The data on 325 patients who underwent spinal surgery were analyzed. Data on 177 patients of the retrospective group who underwent spinal surgery without infectious complications were compared with the data of patients who had local complica- tions of infectious genesis within one year after the operation (36 observations). Results. The study resulted in creation of a learning matrix which became the basis for mathematical prediction and algorithm for the prevention of local infectious complications in patients who underwent spinal surgery. Seventeen criteria for predicting the development of surgical site infection were identified. Conclusion. Approbation of the program in a prospective study (112 cases) with a follow-up period of 12 months after surgery demonstrated significant decrease in the incidence of surgical site infection as compared with that in the retrospective study group (from 16.9 to 9.8 %).